No Consequence for Lateral View X-Ray in Displaced Proximal Femoral Fractures in the Elderly - Macke, Christian; Werner, Maic; Herold, Lambert; Krause, Olaf; Graulich, Tilmann; Clausen, Jan-Dierk; Krettek, Christian; Liodakis, Emmanouil (Frontiers in Surgery, 2021)
Background: Due to demographic changes proximal femoral fractures (PFF) in the elderly rise constantly. The standard diagnostic tool is still the x-ray of the pelvis/hip in two planes. Our hypothesis was, that the lateral view x-ray has little influence in classification, planning of the operative procedure and choice of implant in geriatric patients. Methods: Retrospective analysis of all initial x-rays of PFF in geriatric patients (≥70 years) from May 2018 until August 2019 in a Level I Trauma center. Three experienced consultants categorized the fractures on the ap pelvis view and performed Garden and Pauwels classification as well as a two staged classification displaced/nondisplaced (for femoral neck fractures (FNF)) or AO Classification (for intertrochanteric fractures (ITF)). Afterwards they decided the operative strategy as well as implant choice (dynamic hip screw (DHS), intramedullary nail (IMN) or arthroplasty). After four weeks they categorized all fractures again with now available lateral view x-rays in a different order. Results: 207 patients (146 female, 61 male; 70.5% vs 29.5%) with 90 FNF and 117 ITF (43.5% vs 56.5%) could be included. Age was 84,6 ± 6,9 years. The treatment was in 45 cases DHS, in 82 cases IMN and for the other 80 cases arthroplasty. The interobserver reliability of the classifications were poor, except for the two staged classification (Fleiss- ap view only= 0.708 (CI 95% 0.604;0.812) vs additional lateral= 0.756 (CI 95% 0.644;0.869)). Moreover, independent from the classification, there were no significant changes in management and choice of implant with additional lateral view. Conclusions: Regarding our results we consider the lateral view dispensable for standard x-ray of displaced PFF in geriatric patients. In nondisplaced fractures it could be added secondary.